Hak Warisan Wanita dalam Perspektif Hukum Islam: Kajian Sosial Hukum Islam - Halimi, Moh. Zunaidi (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2025)
Background. The issue of women’s inheritance rights has long been a subject of discussion in Islamic law. Although the Qur’an establishes a ratio of two-to-one between male and female heirs, many modern scholars and feminists challenge this provision, arguing for equal inheritance based on justice and social changes.Aim. This study aims to analyze the development of female inheritance rights within the framework of Islamic law, focusing on socio-historical factors and debates that have shaped its evolution, and to predict possible directions for its future interpretation.Methods. This research employs a library-based qualitative approach (library research) by examining classical fiqh literature from the four schools of thought and comparing them with contemporary interpretations and gender justice discourses.Results. The study finds that the classical formulation of 2:1 emerged during the socio-historical context of a patriarchal society, in which women had minimal public and economic roles. However, in contemporary contexts, where women increasingly contribute to family and public life, scholars propose more egalitarian approaches, either through reinterpretation or consensual redistribution mechanisms such as hibah and shadaqah. The study recommends a mediating framework between textual and contextual readings to achieve both fidelity to scripture and social justice.